Development of magneto-responsive hydrogel networks for neural tissue engineering - Jordan Roe (2022)
Parkinsons Disease is an incurable and debilitating disease, characterised by a loss of dopamine producing neurons in a specific area of the mid brain (substantia nigra). There is a need for a regenerative approach to address the gradual degeneration of dopaminergic neurons, as the gold standard pharmacotherapies focus solely on limiting the effects of motor-based symptoms. The following project aims to generate a material using a synthetic chemistry approach that is able to culture immature neural cells in vitro, with a specific focus on developing material properties which recapitulate those found in human brain tissue. Secondly, a responsive element is integrated into the material, providing switchable stiffness properties that will allow the manipulation of neural circuits in a clinical environment. A description of the need for synthetic biomaterials to treat neurodegenerative diseases is detailed in Chapter 1, followed by a detailed description of the methods used within this research in Chapter 2. In Chapter 3, the composition of synthetic hydrogel pre-polymer solutions are varied to optimise the material properties of resulting hydrogels made through free radical polymerisation. Hydrogels were shown to reach storage moduli between 2.5 – 40,000 Pa, upon modification to pre-polymer solution crosslinker density. Moreover, preliminary cell compatibility investigations provide insight into the difficulties encountered with 3-dimensional cell culture, as cells are initially observed to avoid adhering to un-modified hydrogels. Superparamagnetic nanoparticles are developed and characterised in Chapter 4, as a magneto-responsive element to be combined with hydrogels developed in Chapter 3. Iron oxide nanoparticles are coated sequentially with a polymer and gold layer, producing hybridised magnetic nanoparticles (80 nm) that display superparamagnetic behaviour. Biocompatibility of the nanoparticles is tested with an immature neural cell line at each stage of the coating process, identifying a cytotoxic effect of the intermediate polymer coating, which is reduced upon addition of the final gold layer. Finally, tuneable hydrogels produced in Chapter 3 are combined with hybridised nanoparticle developed in Chapter 4, to produce magneto-responsive ferrogels that are characterised and optimised in Chapter 5. Ferrogel shape, nanoparticle dispersity, and biocompatibility, are optimised to produce magneto-responsive hydrogels that can be further customised using 3D printing.  This study highlights the many steps involved in developing and characterising a novel biomaterial, and focuses largely on the optimisation of scaffold material properties to facilitate the growth of neural cells in vitro. A superparamagnetic responsive element is incorporated into these synthetic hydrogels, providing wide-ranging potential in the field of tissue engineering. Moreover, production of unique geometries using 3D printing, coupled with the tuneability of the hydrogel properties, could allow for more tissue constructs to be replicated, providing a regenerative treatment for multiple diseases. This work presents the creation of a new generation of advanced materials, which will enable the researchers globally to pursue regenerative medicine strategies otherwise unachievable through conventional means.